A new species of mite in the genus Nenteria (Uropodina, Trematuridae), with a key to the Egyptian species - Abo-Shnaf, Reham; Allam, Sally F.m.; Othman, Nehal A.a. (Zootaxa, 2024)
We describe a new species of mite in the genus Nenteria Oudemans, collected from the Red Palm Weevil, Rhynchophorus ferrugineus (Oliver) (Coleoptera: Curculionidae), at Bahariya Oasis, Egypt. Nenteria bahariyaensis n. sp. is the third species from this genus reported from Egypt, after Nenteria hypotrichus El-Borolossy & El-Banhawy, 1995 and N. egypticus (Abo-Shnaf, El-Bishlawy & Allam, 2018). A key to separate those species is provided. This work considers the possibility of using this mite species in integrated control approaches for R. ferrugineus.